Hormone-induced sperm-release in the critically endangered Booroolong frog (Litoria booroolongensis): effects of gonadotropin-releasing hormone and human chorionic gonadotropin. Issue 1 (5th February 2019) - Silla, Aimee J; McFadden, Michael S; Byrne, Phillip G
Abstract : Reproductive technologies have great potential to overcome captive breeding failure and improve the propagation and genetic management of threatened species. Here we report on the development of hormone therapies to induce sperm-release in the critically endangered Booroolong frog, Litoria booroolongensis . Abstract: Research into the development of reproductive technologies for amphibians has increased in recent years due to the rapid decline of amphibian species globally. Reproductive technologies have great potential to overcome captive breeding failure and improve the propagation and genetic management of threatened species. However, the incorporation of these technologies into conservation breeding programs has been protracted, primarily as a result of trial-and-error approaches to the refinement of hormone therapies. The present study investigated the effects of: (1) GnRH-a dose (0, 0.5, 1, 2, 4, 8 or 16 μg g −1 ), and (2) hCG dose (0, 2.5, 5, 10, 20 or 40 IU g −1 ), on the sperm-release response of the critically endangered Booroolong frog. Administration of GnRH-a at a dose of 0.5 μg g −1 resulted in the greatest number of sperm released (mean total sperm = 3.5 ×10 6, n = 11). Overall, hCG was more effective at eliciting spermiation in Booroolong frogs, with peak sperm release (mean total sperm = 25.1 ×10 6, n = 10) occurring in response to a dose of 40 IU g −1 . Sperm output in response to 40 IU g −1 hCG was greatest between 1 and 6 h and steadily declined between 8 and 24 h post-hormone administration. Percent sperm motility peaked between 4 and 10 h (58.1–62.7%), and sperm velocity between 4 and 12 h (24.3–27.2 μm s −1 ). Booroolong frogs join a small, but growing number of amphibian species that exhibit improved spermiation in response to hCG. Further research is required to identify optimal hormone-induction protocols for threatened amphibians and expedite the incorporation of reproductive technologies into CBPs.